Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Step 1: Convert to slope-intercept form to find the slope of the line.
This isn't necessary if you know all the shortcuts, it just makes your life a bit easier.
[tex]3x+6y-1=0\\6y=-3x+1\\y=-\frac{3}{6}x+\frac{1}{6}\\-\frac{1}{2}x+\frac{1}{6}[/tex]
Now we want to find the equations for our new lines. It's easiest to do this in slope-intercept form, so let's start finding the slope and y-intercept.
So for the perpendicular line, the slope is going to flip and change signs, this is aka its opposite reciprocal.
And for the parallel line, it'll stay the same.
[tex]-\frac{1}{2}[/tex] ⇒ [tex]\frac{2}{1}=2[/tex]
[tex]-\frac{1}{2}[/tex] ⇒ [tex]-\frac{1}{2}[/tex]
As for the y-intercept, just apply that slope until you get a point where x=0.
(5, 1) with a rise of 2 and a run of 1...let's work backwards to (0, b)
(5, 1), (4, -1), (3, -3), (2, -5), (1, -7), (0, -9).
(5, 1) with a rise of -1 and a run of 2...let's work backwards to (0, b)
(5, 1), (3, 0), (1, -1)...gonna have to take half a step here...(0, -1.5).
Now let's construct our equations in slope-intercept form.
[tex]y = 2x-9\\y=-\frac{1}{2}x-\frac{3}{2}[/tex]
And now it's time to convert to general form!
Make sure we have common denominators...check.
Multiply by the denominator...
[tex]y=2x-9\\2y=1x-3[/tex]
...check.
Aaaand bring everything over!
[tex]\boxed{-2x+y-9=0}\\\boxed{-x+2y-3=0}[/tex]
This isn't necessary if you know all the shortcuts, it just makes your life a bit easier.
[tex]3x+6y-1=0\\6y=-3x+1\\y=-\frac{3}{6}x+\frac{1}{6}\\-\frac{1}{2}x+\frac{1}{6}[/tex]
Now we want to find the equations for our new lines. It's easiest to do this in slope-intercept form, so let's start finding the slope and y-intercept.
So for the perpendicular line, the slope is going to flip and change signs, this is aka its opposite reciprocal.
And for the parallel line, it'll stay the same.
[tex]-\frac{1}{2}[/tex] ⇒ [tex]\frac{2}{1}=2[/tex]
[tex]-\frac{1}{2}[/tex] ⇒ [tex]-\frac{1}{2}[/tex]
As for the y-intercept, just apply that slope until you get a point where x=0.
(5, 1) with a rise of 2 and a run of 1...let's work backwards to (0, b)
(5, 1), (4, -1), (3, -3), (2, -5), (1, -7), (0, -9).
(5, 1) with a rise of -1 and a run of 2...let's work backwards to (0, b)
(5, 1), (3, 0), (1, -1)...gonna have to take half a step here...(0, -1.5).
Now let's construct our equations in slope-intercept form.
[tex]y = 2x-9\\y=-\frac{1}{2}x-\frac{3}{2}[/tex]
And now it's time to convert to general form!
Make sure we have common denominators...check.
Multiply by the denominator...
[tex]y=2x-9\\2y=1x-3[/tex]
...check.
Aaaand bring everything over!
[tex]\boxed{-2x+y-9=0}\\\boxed{-x+2y-3=0}[/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.